2014
DOI: 10.1152/japplphysiol.00880.2013
|View full text |Cite
|
Sign up to set email alerts
|

AltitudeOmics: cerebral autoregulation during ascent, acclimatization, and re-exposure to high altitude and its relation with acute mountain sickness

Abstract: Cerebral autoregulation (CA) acts to maintain brain blood flow despite fluctuations in perfusion pressure. Acute hypoxia is thought to impair CA, but it is unclear if CA is affected by acclimatization or related to the development of acute mountain sickness (AMS). We assessed changes in CA using transfer function analysis of spontaneous fluctuations in radial artery blood pressure (indwelling catheter) and resulting changes in middle cerebral artery blood flow velocity (transcranial Doppler) in 21 active indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 40 publications
(78 reference statements)
2
37
1
Order By: Relevance
“…1), a threshold of ARI < 4 could still be considered appropriate in situations where investigators want to favour sensitivity, in detriment of specificity, to identify patients that might be at risk of secondary damage due to weakening of CA. This threshold correlates well with studies that have reported abnormality of dCA in patients with severe head injury (Panerai et al 2004), carotid artery disease (Panerai et al 1998b), stroke (Salinet, Panerai & Robinson 2014, Saeed et al 2013), high altitude depression of CA (Subudhi et al 2014) and other conditions (Panerai 2008). …”
Section: Normative Valuessupporting
confidence: 89%
“…1), a threshold of ARI < 4 could still be considered appropriate in situations where investigators want to favour sensitivity, in detriment of specificity, to identify patients that might be at risk of secondary damage due to weakening of CA. This threshold correlates well with studies that have reported abnormality of dCA in patients with severe head injury (Panerai et al 2004), carotid artery disease (Panerai et al 1998b), stroke (Salinet, Panerai & Robinson 2014, Saeed et al 2013), high altitude depression of CA (Subudhi et al 2014) and other conditions (Panerai 2008). …”
Section: Normative Valuessupporting
confidence: 89%
“…Many studies have concluded that autoregulation is impaired at HA (e.g., ref. 25), although this is not a universal finding and surely relates to lack of a consensual metric for the quantification of CA. 26 A number of studies have found an important function of the sympathetic nervous system in attenuating surges in CBF (reviewed in ref.…”
Section: Relationship Between Enhanced Mean Arterial Pressure Reactivmentioning
confidence: 92%
“…Disturbed autoregulation may occur in AMS [35,46] and could enhance pressure transduction to the brain, although findings are controversial [47]. Repeated transient increases of ICP may sensitise trigeminal nociception [48] and decrease compliance of the CNS to a variable degree, since the capacity for spatial compensation varies considerably between individuals [49].…”
Section: The Brainmentioning
confidence: 99%